The Arthur Hailey Collection - Lundstrom, Thomas (International Journal of Bahamian Studies, 2013)
The Arthur Hailey collection at the Harry C. Moore Library of the College of The Bahamas contains over 800 items from Hailey’s home at Lyford Cay, New Providence. This collection of commercially published editions of his work is a resource that scholars may use for research on this bestselling author.